NILAI NILAI SOSIAL DALAM TRADISI MAPPANRE TEMMEâ DI KECAMATAN TANETE RILAU, KABUPATEN BARRU - Mundzir, Chaerul (RIHLAH, 2014)
Procession of completing the Quran (Khatam), maybe for some people is a common tradition and less interested to be discussed in a study. However, it should be understood that the appreciation of the procedures for completing the Quran that make this tradition should be interested to be discussed, because the Quran is the major source and soul for all of Muslims. Therefore, it is necessary to explore further the tradition of Mappanre Temme, especially for the Bugis community at the District of Tanete Rilau, Barru. Mappanre Temmeâ is a tradition that was born as a result of Islamization at the Kingdom of Tanete in the 17th century and the creativity of the Bugis community also, which was born from the deep Islamization of society. So, it would be appears the appreciation of Procession of completing the Quran (Mappanre Temmeâ Tradition).Implementation of this tradition isnât only produce the motivation to continue read the Qurâan. In the end, it should give an effect on the life of society, as in the Mappanre Temme tradition there are a few of social values to live in the social life now.